Amomum nimkeyense (Zingiberaceae), a new species from Arunachal Pradesh, northeastern India - Sabu, Mamiyil; Hareesh, Vadakkoot Sankaran; Mibang, Tatum; Das, Arup Kumar (Phytotaxa, 2018)
Amomum nimkeyense, a new species is described from Arunachal Pradesh, northeastern India. A detailed description of the plant, distribution and ecology along with colour photographs are provided for ease of identification.